Cryoballoon atrial fibrillation ablation: Single-center safety and efficacy data using a novel cryoballoon technology compared to a historical balloon platform - Kochi, Adriano N; Moltrasio, Massimo; Tundo, Fabrizio; Riva, Stefania; Ascione, Ciro; Dessanai, Maria A; Pizzamiglio, Francesca; Vettor, Giulia; Cellucci, Selene; Gasperetti, Alessio; Tondo, Claudio; Fassini, Gaetano (Journal of Cardiovascular Electrophysiology, 2021)
INTRODUCTION: Catheter ablation is superior to drugs regarding atrial fibrillation (AF) recurrence, symptoms improvement, and mortality reduction in heart failure. POLARx is a novel cryoballoon, with technical improvements seeking to improve outcomes. So far, its clinical evidence is restricted to a case report.METHODS: To compare the POLARx cryoballoon procedural safety and efficacy to the already established Arctic Front Advance PRO (AFAP) in a single-center cohort study, consecutive patients undergoing AF cryoablation with the POLARx were enrolled. Data were prospectively gathered. POLARx patients were compared with a historical cohort of patients submitted to AF cryoablation with the AFAP.RESULTS: Seventy patients were analyzed, 20 in POLARx, and 50 in the AFAP group. They all underwent first-time pulmonary vein isolation, 77% were male, 94% had paroxysmal AF, median age was 62.5 years, median CHA2 DS2 -VASc 1, left-atrium size 34ml/m, and 65% were receiving anticoagulation. The primary end-point, all pulmonary veins isolation, was 100% in both groups. The complication rate was similar (0% POLARx vs. 5.7% AFAP, p=.39). The median total procedural time was longer in the POLARx group (90min vs. 60min, p<.001), but the overall time-to-isolation (TTI; 44.8s vs. 39s, p=.253) and ablation time (15min vs. 13.7min, p=.122) was similar between POLARx and AFAP groups, respectively. Despite equal TTI, the POLARx had a lower minimal temperature reached (-57°C vs -47°C, p<.001).CONCLUSION: The novel POLARx cryoballoon had similar efficacy and safety compared with the AFAP. It was also associated with longer procedural times, similar TTI, and lower minimum temperature reached.